Factors associated with chronic kidney disease in patients with diabetes in French Guiana - Sacareau, Christopher; Nacher, Mathieu; Drak Alsibai, Kinan; Ntoutoum, Andre; Adenis, Antoine; Hounnou, Marianne; Liebart, Marion; Cardoso, Clara Salasar; Aurelus, Jean-Markens; Demar, Magalie; Casse, Olivier; Amokrane, Samia; et al. (Frontiers in Clinical Diabetes and Healthcare, 2023)
Introduction: With over half of the population living under the poverty threshold, the social and health context in French Guiana is more difficult than in mainland France.. The prevalence of diabetes is twice as high increased twofold and that of end-stage renal failure is 45% higher than in in mainland France. Objective: Our objective was to describe the profile of diabetic patients with chronic kidney disease in French Guiana and search for possible risk factors. Method: We conducted a multicenter cross-sectional observational study based on the CoDiam cohort. We analyzed 1287 patients followed up between May 2019 and June 2021 at Cayenne hospital, Saint Laurent hospital and Delocalized Health Centers. Results: In our cohort, chronic kidney disease was present after an average of 12 years of diabetes. Compared to the French population, 41% of diabetic patients had chronic kidney disease (i.e. 12% more), with an average of 56 years of ageold (i.e. 10 years younger). 48% of these patients were obese (i.e. 7% more). Precariousness concerned 74% of the patients were precarious, and foreign origin concerned 45% of the patientswere foreigners but neither was associated with chronic kidney disease, contrary to countries where the health system is not universal. Conclusion: Screening of patients with chronic kidney disease among diabetics in French Guiana remains a real challenge. Patients were younger and more obese than in other French territories. In this cohort, precariousness and immigration were not associated with the presence of chronic kidney disease. However, particular attention should be paid to hypertensive diabetic patients and those over 65 years of age, which are, with diabetes itself, the two most obvious risk factors for developing chronic kidney disease among diabetic patients in our territory.